2020
DOI: 10.1016/j.molliq.2020.112701
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of aqueous solutions of ethaline deep eutectic solvent

Abstract: We have established a detailed phase diagram of a prototypical DES as a function of the hydration level. Two distinct thermal phase behaviors are observed depending on the water content with respect to a cross-over composition W g ' = 30%. For W < W g ', the formation of ice is not observed under the experimental conditions used in this study, and the solution falls in the category of glassforming systems. Fully vitreous states could also be obtained between 30% and 50%, but they are metastable with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…2 displays the heating regime of representative DSC traces, recorded according to the procedure described in the ESI. † Similar to the observations of Jani et al, 21 for all studied mixture compositions crystallization did not occur during cooling. However, all samples, including neat ethaline, crystallized during the subsequent isothermal holding step.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…2 displays the heating regime of representative DSC traces, recorded according to the procedure described in the ESI. † Similar to the observations of Jani et al, 21 for all studied mixture compositions crystallization did not occur during cooling. However, all samples, including neat ethaline, crystallized during the subsequent isothermal holding step.…”
supporting
confidence: 91%
“…1). Recent publications of Alfurayj et al 20 and Jani et al 21 revealed a strong impact of moderate amounts of water on various physical properties of ethaline (x ChCl = 0.333), including heat flow. We observed that in ethaline containing less than 3000 ppm of water ChCl crystals form at room temperature, see Fig.…”
mentioning
confidence: 98%
“…For practical reasons, aqueous solutions of DESs have been formulated and their physical properties, including excess properties, viscosity, acoustic, structural and optical properties have been studied thoroughly. [9][10][11][12][13][14][15][16][17][18][19][20][21] These works have also raised the question of the resilience of the specific local arrangement of DES during dilution with water and its evolution towards an aqueous solution of its constituents. 9-11, 19, 22 The structure of DESs has attracted a lot of interest during the last four years.…”
Section: Introductionmentioning
confidence: 99%
“…11 The rational design and selection of DESs for a particular process require general knowledge and consideration of the properties of DESs, thus increasing attention is being paid to experimentally and analytically understand their properties, such as melting temperatures, density, surface tension, speed of sound, and conductivity. [12][13][14][15] Melting temperature, as one of the most important physical properties, is useful in chemical identification, 16 purification, 17 and drug research. 18 In addition, the properties, experimentally difficult to determine, for example, enthalpy of fusion and activity coefficient, 19 can also be derived from melting temperature data.…”
mentioning
confidence: 99%